Maimon on the (In-)dispensability of the Kantian Thing in Itself: A Misleading Narrative - Marialena Karampatsou (Journal of Modern Philosophy)
The Kantian thing in itself has been the subject of a centuries-old debate, toward which Salomon Maimon––following the standard interpretation––is thought to make the first “forward-looking” move: Maimon is interpreted as the first proponent of the redundance of a commitment to the mind-independent world, thus inaugurating a new era in the reception of Kant’s idealism. Against this influential narrative, I argue that Maimon’s views are motivated by a combination of skepticism and explanatory rationalism, which is fully compatible with realism and does not entail the dispensability of the mind-independent world. This has interesting and important implications for Maimon’s overall reading of Kant and for his place in the history of German philosophy.